Alopecia areata. Diagnostic and therapeutic recommendations of the Polish Society of Dermatology. Part 2: Treatment - Adriana Rakowska; Lidia Rudnicka; Małgorzata Olszewska; Beata Bergler-Czop; Joanna Czuwara; Ligia Brzezińska-Wcisło; Joanna Narbutt; Waldemar Placek; Barbara Zegarska (Termedia Publishing House, 2023)
The treatment goal in alopecia areata is induction of hair regrowth and halting the progression of the disease. Treatment decisions depend on the severity of the alopecia areata as assessed by the Severity of Alopecia Tool (SALT) or the Alopecia Areata Scale (AAS). In mild alopecia areata, very ultra-high potency topical glucocorticoids and intralesional triamcinolone acetonide are the mainstay of treatment. In moderate to severe alopecia areata, systemic treatment is usually required. Currently, the only drug dedicated for alopecia areata, approved in Europe and the United States is baricitinib. Ritlecitinib, a JAK3/TEC inhibitor is approved in the United States for individuals 12 years of age and older with severe alopecia areata and is expected to be approved in Europe soon. Other systemic medications used in alopecia areata include glucocorticoids, cyclosporine, and methotrexate. Contact immunotherapy may be considered. In alopecia areata, long-maintenance treatment is of substantial significance.